Students’ Voices on Lecturers’ Written Corrective Feedback (WCF) in Their Writing Tasks - Adrefiza Adrefiza; Didin Nuruddin Hidayat; Fortunasari Fortunasari (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
ABSTRACTAlthough studies on Written Corrective Feedback (WCF, hereafter) have been increasingly prevalent in the last few years, inquiries on how advisory students perceive the lecturers’ feedback on their writing tasks have been likely scarce, especially in Indonesian Higher Education Institutions (HEIs) contexts. This study examines the students’ perception and evaluation of the lecturers’ WCF in response to errors and inaccuracies in their academic writing tasks. Through an online survey questionnaire distributed to 46 respondents via email, the results show that the majority of students appreciated any forms of feedback from the lecturers. Their writing skills in four aspects (grammar, vocabulary, organization, and mechanics) also improved significantly through an enhancement of their self-directed learning. Following the analysis model by one of previous studies, the results showed that the students preferred direct WCF to the Indirect one (58.7 %: 15.2 %), while the “Praise” category was given the highest rate with an average score of (4.06). “Criticism”, on the other hand, was the lowest one with an average score of only (2.3) in the evaluation. It is recommended that lecturers always avoid unclear, vague, aggressive, thoughtless, and inappropriate feedback to improve students’ writing skills and performance. ABSTRAKMeskipun studi tentang Umpan Balik Korektif Tertulis (WCF, selanjutnya) semakin lazim dalam beberapa tahun terakhir, namun, diskusi tentang penilaian mahasiswa terhadap umpan balik dosen terkait tugas menulis mereka sangat terbatas, terutama dalam konteks Lembaga Pendidikan Tinggi Indonesia (PT). Penelitian ini mengkaji persepsi dan evaluasi mahasiswa terhadap WCF dosen dalam merespon kesalahan dan ketidaktepatan dalam tugas menulis akademik mahasiswa. Melalui kuesioner survei online yang dibagikan kepada 46 responden melalui email, hasilnya menunjukkan bahwa mayoritas mahasiswa mengapresiasi segala bentuk umpan balik dari dosen. Keterampilan menulis mereka dalam empat aspek (tata bahasa, kosakata, organisasi, dan mekanik) juga meningkat secara signifikan melalui peningkatan pembelajaran mandiri mereka. Mengacu kepada model analysis dari salah satu penelitian terdahulu, ditemukan bahwa penggunaan WCF Langsung lebih disukai oleh siswa daripada penggunaan Tidak Langsung (58,7%: 15,2%), sedangkan kategori “Pujian” diberikan nilai tertinggi dengan nilai rata-rata (4,06). Sementara, “Kritik” adalah yang paling rendah dengan skor rata-rata hanya (2,3) dalam evaluasi. Disarankan agar dosen selalu memberikan semangat, namun hindari umpan balik yang tidak jelas, kabur, agresif, ceroboh, dan tidak tepat untuk meningkatkan kemampuan menulis dan prestasi mahasiswa.